Ensino de libras como língua adicional: estratégias e recursos didáticos - Ribeiro, Maria Clara Gandini (Universidade Federal de São Carlos, 2025)
The objective of this study is to analyze the teaching resources and strategies employed in a Brazilian Sign Language (Libras) as a second language course for hearing students at a university in the state of São Paulo, Brazil. More specifically, the study examines how these resources contributed to the acquisition of basic Libras by hearing students with no prior knowledge of the language, as determined by the instructor during the first class. This study draws on previous research on the teaching and learning of Libras in formal educational settings, highlighting the role of different resources in the acquisition of a visual-spatial language, with particular emphasis on SignWriting as one of the resources that support language acquisition (LEITE; MCCLEARY, 2009; BLANC, 2022). The methodology adopted was based on Leite and McCleary (2009), who conducted a diary-based study observing classes in Libras as a second language taught by deaf instructors at the basic, intermediate, and advanced levels. The present study focuses exclusively on the basic level. The analysis of the teaching materials indicated that the use of multiple teaching resources plays an important role in promoting more effective language acquisition.
Teaching brazilian sign language (Libras) as an additional language: strategies and teaching resources
Keywords: Escrita de sinais; SignWriting; Libras; Ensino de língua adicional; Additional language teaching; LINGUISTICA, LETRAS E ARTES::ARTES; 4. Educação de Qualidade